Initial Reports of the Deep Sea Drilling Project 1985
DOI: 10.2973/dsdp.proc.84.129.1985
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Analysis of Core Gases at Sites 565-570, Deep Sea Drilling Project Leg 84

Abstract: Methane carbon-isotopic compositions (δ 13 C values relative to the PDB standard) at Sites 565, 566, 567, and 569 were lighter (enriched in 12 C) than-60‰, indicating a biogenic origin. In the deeper sections at Sites 568 and 570, δ 13 C values were heavier, approaching-40‰, and therefore suggest a thermogenic source. A significant thermogenic source was discounted, however, because the carbon dioxide δ 13 C values in these sections were also anomalously heavy, suggesting that the methane may have formed bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The 613C values of methane in marine sedi ments become generally heavier with depths par allel to depth-trends of 613C values of co-existing carbon dioxide in regions where gas hydrates are found (Claypool and Kaplan, 1974;Galimov and Kvenvolden, 1983;Jeffrey et al, 1985;Claypool et al, 1985;Kvenvolden and Kastner, 1990). Similar patterns of the 613C change with depth are also observed in regions where gas hydrates are not stable, such as Cariaco Trench (Claypool and Kaplan, 1974).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The 613C values of methane in marine sedi ments become generally heavier with depths par allel to depth-trends of 613C values of co-existing carbon dioxide in regions where gas hydrates are found (Claypool and Kaplan, 1974;Galimov and Kvenvolden, 1983;Jeffrey et al, 1985;Claypool et al, 1985;Kvenvolden and Kastner, 1990). Similar patterns of the 613C change with depth are also observed in regions where gas hydrates are not stable, such as Cariaco Trench (Claypool and Kaplan, 1974).…”
Section: Introductionsupporting
confidence: 62%
“…The more abundant organic carbon should relate to prolonged and vigorous methanogenesis, resulting in 13C_ depletion in the CO2 reservoir from which the CH4 was formed. The isotopically heavy methane (--40%0) in gas hydrate was found at Site 570 on DSDP Leg 84 offshore Guatemala (Table 1), ac companied by isotopically heavy CO2 (Jeffrey et al, 1985;Claypool et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…At sub-bottom depths greater than those sampled at Leg 96 sites, ethane and other C 2 -C 5 hydrocarbons were detected (Galimov et al, 1980;Schoell, 1982). In contrast, core gas-pocket studies in the Japan Trench (Whelan and Sato, 1980), California Basin (Galimov and Simoneit, 1982), and Middle America Trench (Jeffrey et al, 1985) found C 2 -C 5 hydrocarbons at most depths where gas pockets were sampled. The processes controlling the amount of C 2 -C 5 hydrocarbons in shallow sediments containing primarily biogenic gas are unclear.…”
Section: Resultsmentioning
confidence: 99%
“…δ 13 C values of ethane were measured on 13 samples below 200 mbsf at Sites 860 and 861, and one sample at 70 mbsf at Site 863, ranging between -70%o and -AA‰ (Table 1). The δ 13 C values of ethane of core gases from ODP Leg 84, Site 570 are fairly uniform, ranging from -24‰ to -26%o in six sections, indicating a thermogenic origin (Jeffrey et al, 1985), and those values measured on sorbed gases from ODP Leg 112, Sites 679, 680, and 682 range from -38‰ to -25%e for 22 samples except for one data of -48.3‰, also indicating a thermogenic origin (Whiticar and Suess, 1990). Ethanes of this study are depleted in 13 C compared to these data, and the carbon isotope compositions are among the lightest values reported for ethane in natural gas.…”
Section: The δmentioning
confidence: 90%